2019
DOI: 10.3906/elk-1811-177
|View full text |Cite
|
Sign up to set email alerts
|

Energy and economic assessment of major free cooling retrofits for data centersin Turkey

Abstract: Mechanical cooling is responsible for a significant fraction of the energy consumption of data centers (DCs). Free cooling systems take advantage of ambient conditions to reduce the need for compressor-based cooling. This study utilizes thermodynamic models of major free cooling systems such as the direct air-side economizer (ASE), indirect air-side economizer (IASE), indirect evaporative cooler (IEC), and indirect water-side economizer (WSE) integrated with the existing cooling infrastructure of a typical 1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In 2018, an air-cooled CS in Helsinki-Finland was transformed into a liquid-cooled telecommunication equipment, it resulted in 70% annual energy savings and an 80% reduction in CO2 emissions compared to air cooling, with the potential to use 80% of total dissipated energy for heating (Huttunen et al, 2020). The study by Gözcü and Erden (2019), examines the energy consumption of data centres using free cooling systems like the direct air-side economizer , indirect air-side economizer , indirect evaporative cooler , indirect water-side economizer integrated with the existing cooling infrastructure of a typical 1 MW IT load centres. Results showed that indirect evaporative cooler IEC had the most energy-saving potential, reducing chiller hours by less than 10% across Turkey and by 1% in half of the cities studied.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…In 2018, an air-cooled CS in Helsinki-Finland was transformed into a liquid-cooled telecommunication equipment, it resulted in 70% annual energy savings and an 80% reduction in CO2 emissions compared to air cooling, with the potential to use 80% of total dissipated energy for heating (Huttunen et al, 2020). The study by Gözcü and Erden (2019), examines the energy consumption of data centres using free cooling systems like the direct air-side economizer , indirect air-side economizer , indirect evaporative cooler , indirect water-side economizer integrated with the existing cooling infrastructure of a typical 1 MW IT load centres. Results showed that indirect evaporative cooler IEC had the most energy-saving potential, reducing chiller hours by less than 10% across Turkey and by 1% in half of the cities studied.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Gozcu et al [29] employed energy simulation to compare the energy use of freecooling systems: a direct air-side economiser, an indirect air-side economiser, an indirect evaporative cooler, and an indirect water-side economiser integrated with the existing cooling infrastructure of a typical 1-MW IT load data centre using the TRNSYS energysimulation program. The indirect air-side economiser with an evaporative cooler yielded the highest annual energy savings; however, it had an increased payback compared to the other technologies analysed.…”
Section: Modelling Data Centres: Advantages Limits and The Gapmentioning
confidence: 99%
“…The indirect air-side economiser with an evaporative cooler yielded the highest annual energy savings; however, it had an increased payback compared to the other technologies analysed. The water-side economiser provided the shortest payback due to its low capital cost [29]. Lee and Chen [30] analysed seventeen climate zones through eQuest energy-simulation software, applying an air-side economiser with enthalpy control to a five-storey data centre.…”
Section: Modelling Data Centres: Advantages Limits and The Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Tablo 5 ekonomik analiz ile ilgili çeşitli kaynaklardan derlenen varsayımları özetlemektedir. Çeşitli veri merkezi iyileştirme yatırımları için literatürde indirgeme oranı olarak %8 ve kullanım ömrü olarak 15-20 yıl varsayılmıştır [30,36,37]. Bu nedenle bu çalışmada da benzer yaklaşım tercih edilmiştir.…”
Section: Bp Modellerinin Tasarım Detayları (Design Details Of the Bp ...unclassified